2013
DOI: 10.1007/s11207-013-0423-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of a Transition Region Bright Point with a Blinker and Coronal Bright Point Using Multiple EIS Emission Lines

Abstract: Since their discovery twenty year ago, transition region bright points have never been observed spectroscopically. Bright point properties have not been compared with similar transition region and coronal structures. In this work we have investigated three transient quiet Sun brightenings including a transition region bright point (TR BP), a coronal bright point (CBP) and a blinker. We use time-series observations of the extreme ultraviolet emission lines of a wide range of temperature T (log T = 5.3 − 6.4) fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…The morphology of the resulting jet is of a bi-directional nature inclined to the LOS as we see the main jet ejecting to the northwest and a smaller one to the south. Although we lack the spectral data that are a signature of bi-directional phenomena Madjarska et al 2004), this uniquely observed sideways morphology, due to the downward magnetic pressure of the overlying horizontal coronal field , suggests a self-similarity between other coronal bi-directional BP events (Orange et al 2014b). In addition, this EUV QS BP sigmoid is predictive of eruptive behavior similar to soft X-ray observations of micro-sigmoids associated with vertical coronal jets (Raouafi et al 2010) and EUV micro-sigmoids leading to micro-CMEs, further demonstrating a multi-scaled selfsimilarity.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The morphology of the resulting jet is of a bi-directional nature inclined to the LOS as we see the main jet ejecting to the northwest and a smaller one to the south. Although we lack the spectral data that are a signature of bi-directional phenomena Madjarska et al 2004), this uniquely observed sideways morphology, due to the downward magnetic pressure of the overlying horizontal coronal field , suggests a self-similarity between other coronal bi-directional BP events (Orange et al 2014b). In addition, this EUV QS BP sigmoid is predictive of eruptive behavior similar to soft X-ray observations of micro-sigmoids associated with vertical coronal jets (Raouafi et al 2010) and EUV micro-sigmoids leading to micro-CMEs, further demonstrating a multi-scaled selfsimilarity.…”
Section: Discussionmentioning
confidence: 87%
“…The eruptions show a major jet feature extending from the northwest end of the BP with a smaller jet emanating from the south (jet lifetime = 05:58 ± 0:26 minutes). This antiparallel motion is an observational analog reminiscent of bi-directional jet dynamics that are often observed in spectral data associated with BP phenomena Madjarska et al 2004;Orange et al 2014b). As there were no available Hinode/EIS data (Culhane et al 2007;Kosugi et al 2007) coinciding with the pointing of this event, it was not possible to observe Doppler signatures for the observed jet.…”
Section: Event Morphologymentioning
confidence: 80%
See 2 more Smart Citations
“…The potential for small QS network cool loops to initiate flaring activity (Chesny et al 2013) suggests that identifying the full ensemble of cool, non-potential structures would allow us to explore the physics of non-potential field formation across broad spatial, temporal, thermal, density, and magnetic energy scales. This is akin to the blinker-bright point dichotomy (Orange et al 2014b), where investigating the same phenomena at different temperatures, and investigating different phenomena at the same temperature, uncovers physical processes that may be self-similar between plasma regimes.…”
Section: Introductionmentioning
confidence: 99%